Atypical manifestations of recent syphilis: study of 19 cases()() - Sardinha, José Carlos (An Bras Dermatol, 2020)
BACKGROUND: Syphilis is one of the most common diseases that start with genital ulcers. Aside from the initial, classic ulcerative lesion of syphilis, called hard chancre, atypical presentations are common, with erosions, erythema, edema, balanitis, and other dermatological manifestations. Associated with initial genital lesions, the presence of inguinal adenopathies is frequent, and the presence of hardened and painless lymphangitis on the dorsum of the penis is rare. OBJECTIVES: To describe atypical penile manifestations in patients with early syphilis. METHODS: The present study reports patients who developed cord-like lesions on the penis. RESULTS: The study included 25 patients with cord-like lesions on the penis; in 19 of those, the diagnosis of syphilis was confirmed. STUDY LIMITATIONS: Small number of patients included. CONCLUSIONS: In view of the findings of the present investigation, it is important to emphasize that all patients who present with cord-like lesions on the penis must undergo a rapid test for syphilis, VDRL, serologies for HIV viral hepatitis B and C and, whenever possible, histopathological and Doppler exams.